Building Inclusive Education: Analysis of PAI Learning Strategies for SLB Phase E and F - Nindy Putri Aprilia; ⁠Rudi Ahmad Suryadi; Saepul Anwar; Asy'ari; ⁠Putri Intan Utami; Utami Qonita Rahmi (Universitas Muhammadiyah Malang, 2025)
Education is a fundamental right for every individual as mandated by the 1945 Constitution. However, several factors hinder its fulfillment, such as teachers ' lack of understanding regarding children with special needs and a curriculum that is not fully aligned with inclusive education principles considering diversity and individual needs. This study aims to analyze the alignment of Islamic Religion Education (PAI) teaching materials for students with special needs in Phases E and F of the Merdeka Curriculum and explore appropriate strategies for implementation in Special Needs Education (ABK). Using a qualitative descriptive approach, data were analyzed based on Miles and Huberman's steps, including data collection, reduction, display, and conclusion drawing. Findings indicate that : (1) PAI objectives, characteristics of each elements, and learning outcomes in Phases E and F are aligned with the needs of SMALB students with an average mental age of ±10 years; (2) teaching requires strategic adjustments and individualized approaches to cater to the specific needs of ABK groups , including those who are visually impaired, hearing impaired, physically disabled, intellectually disabled, emotionally disturbed, autistic, or gifted. These​ strategies significantly enhancing PAI learning, fostering individual with faith, piety, and noble character as mandated by the National Education System Law No. 20 of 2003.